The Use of Skit Technique in Enhancing the Students’ Speaking Ability - Andi Patmasari (Hasanuddin University, 2020)
This research intended to prove whether the use of skit technique enhanced the students’ speaking ability or not. This research employed quasi-experimental research design with the non-equivalent control group design. The population of this research was the second year students of senior high school that consisted of 260 students. This research used cluster random sampling technique. From nine classes, two classes were taken as a sample of the research. One class was chosen as the experimental class and another one as the control class. The total sample consisted of 72 students. In order to answer the research question, the instrument of this research was speaking test. There are some types of oral tests, but this research used a picture story. The result of data analysis showed that the rate percentage and frequency of the post-test score was higher than the rate percentage and frequency of the pre-test score. In pre-test, the value of t-test (0.34) was lower than the value of t-table (1.980). While in post-test, the t-test value (2.83) was higher than the t-table value (1.980). Based on these findings, it can be inferred that the skit technique significantly enhanced the students’ speaking ability.